Cross-cultural adaptation of the Preterm Parenting & Self-efficacy Checklist - Souza Mendes, Carolina Queiroz de; Mandetta, Myriam Aparecida; Tsunemi, Miriam Harumi [UNESP]; Ferreira Gomes Balieiro, Maria Magda (Assoc Brasileira Enfermagem, 2019)
Objective: To conduct a cross-cultural adaptation of the Preterm Parenting & Self-Efficacy Checklist to the Brazilian Portuguese. Method: A methodological study was carried out with 51 parents of premature infants. Data analysis was based on psychometric and inferential statistical analyses. Results: The instrument content validation by experts obtained excellent agreement (97%) and the semantic analysis by the target population showed good understanding of the terms and ease of use. In test-retest, most participants were female (64.7%); and parents with higher education (47.1%). The instrument showed stability over time, with good internal consistency (alpha = 0.84). Four factors were generated in the subscales parenting self-efficacy, importance of tasks and self-perceived parental competence (67.0% to 74.2% of the variance). Conclusion: The properties of the Preterm Parenting & Self-Efficacy Checklist - Brazilian Version were maintained, which is a reliable indicator to evaluate the hospital discharge of premature infants.
Keywords: Self-efficacy; Parents; Infant; Premature; Validation Studies; Neonatal Nursing